Hubungan antara Ekspresi Vascular Endothelial Growth Factor (VEGF) dengan Karakteristik Klinikopatologik Karsinoma Payudara Duktal Invasif - Huratio Nelson; Heni Maulani; Aida Farida; Irsan Saleh (Majalah Patologi Indonesia, 2014)
Background Breast cancer is the most common malignancy and related death of female worldwide. The angiogenesis has an important role in the invasive ductal mammary carcinoma carcinogenesis, and vascular endothelial growth factor (VEGF)is a primary angiogenic factor. The aim of this study is to determine the relationship between the VEGF expression and clinicopatologic characteristics of the invasive ductal mammary carcinoma. Methods It was a cross-sectional study. Fifty-five parafin block samples of mastectomy tissue diagnosed as invasive mammary ductal carcinoma were obtained from the archieves of the Anatomical Pathology Department of RSMH, was stained by immunohistochemical method with anti-VEGF antibody. The result was analyzed in relation to age, tumor size, lymph node status, and histological grade. Results The positivity of VEGF expression was more common in the ≤49 years age of group, in the tumor of ≥9,6 cm size group, in the positive lymph node status, and in the high histological grade. There was a significant correlation between the VEGF expression and the category of lymph node status (p=0.047), as well as histological grade (p=0.020). There was unsignificant correlation between VEGF expression and the age category (p=0.781), as well as tumor size category (p=0.700). Conclusion There was correlation between VEGF expression and lymph node status and histological grade in invasive ductal mammary carcinoma. Key words: clinicopathologic characteristics, invasive ductal mammary carcinoma, VEGF.